Graphics' design work: service / Krizel Wilson - Wilson, Krizel (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
The main concern is that Orchid Park is not easily identifiable due to the dearth of a logo. Orchid Park’s lack of a logo causes it hard to be identified by visitors. To overcome this issue, a minimalistic and an exclusive concept of corporate logo to represent the organization's identity is developed. To attract more visitors, printed advertisement on banners will be used along with short multimedia animation on our website. Located across a waterfront, Orchid Park is an ideal location for tourist attraction.